Investigating the Erα and Cyclin D1 Gene Expression Levels, Changes in SOD, NO, and MDA Levels, and Histopathology of Mice Testicular Tissue Treated with AFG1 - Toraj Zamir-nasta; Seyran Kakebaraei; Mona Pazhouhi; Cyrus Jalili (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Previous studies have shown the adverse effects of aflatoxin G1 on testicular tissue and the process of spermatogenesis. The aim of this study was to investigate changes in the expression of Cyclin D1, the estrogen receptor ERα and the levels of nitric oxide (NO), superoxide dismutase (SOD), and malondialdehyde (MDA) in testicular tissue following exposure to AFG1. Materials and methods: Twenty four mice were divided into four groups (n=6 per group); a control group (saline) and three treatment groups to receive AFG1 for 7, 15, and 28 days intraperitoneally. Histopathological changes caused by this toxin along with the expression of Cyclin D1 and Erα, as well as Nitric oxid (NO), superoxide dismutase (SOD), and malondialdehyde (MDA) levels in testicular tissue were measured. Results: The expression of Cyclin D1 in testicular tissue in AFG1 receiving groups increased in a time-dependent manner and the expression of ERα decreased in testicular tissue in AFG1 receiving groups (P<0.05). Also, AFG1 decreased the level of SOD in testicular tissue in a time-dependent manner and increased the levels of MDA and NO. Atrophy of the seminiferous tubules and extensive intercellular edema were seen in treatment groups compared to the control group. Conclusion: AFG1 disrupts the process of cell division by atrophy of spermatozoa tubules in testicular tissue. It also reduced the expression of ERα receptors and increased the expression of Cyclin D1 along with decreasing the level of SOD in testicular tissue and increased MDA and NO levels. These factors can cause disorders in the process of spermatogenesis.